My brother is a big, fat liar - Patterson, James, 1947-; Papademetriou, Lisa.; Swaab, Neil (New York : Little, Brown, 2013)
Georgia Khatchadorian plans to excel at Hills Village Middle School in all the places her troublemaking brother failed.
School Library Journal, May 2013.
Horn Book, November 2013.
School Library Journal.
Horn Book.
4.1
3-6
Keywords: Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Popularity -- Juvenile fiction; Human behavior -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Middle schools -- Fiction; Schools -- Fiction; Popularity -- Fiction; Behavior -- Fiction; Brothers and sisters -- Fiction; Humorous stories; Cartoons and comics; Middle schools -- Fiction; School stories; Popularity -- Fiction; Human behavior -- Fiction; Siblings -- Fiction; Humorous fiction; Comic books, strips, etc; Middle schools -- Fiction; Popularity -- Fiction; Behavior -- Fiction; Brothers and sisters -- Fiction; Humorous stories; Humorous fiction